2010
DOI: 10.1074/jbc.m110.150664
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoplasmin Binds Histone H2A-H2B Dimers through Its Distal Face*

Abstract: Nucleoplasmin (NP) is a pentameric chaperone that regulates the condensation state of chromatin extracting specific basic proteins from sperm chromatin and depositing H2A-H2B histone dimers. It has been proposed that histones could bind to either the lateral or distal face of the pentameric structure. Here, we combine different biochemical and biophysical techniques to show that natural, hyperphosphorylated NP can bind five H2A-H2B dimers and that the amount of bound ligand depends on the overall charge (phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
68
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(78 citation statements)
references
References 39 publications
10
68
0
Order By: Relevance
“…diluting the histones from 2 M NaCl solutions, were subjected to trypsin treatment, and the resulting fragments were analyzed by MS. As controls, isolated eNP (Figure 5A; lanes 1 and 2) and H3-H4 (Figure 5A; lanes 3–5) were also digested. Data show, as previously found for H2A-H2B (21), that histones were extensively digested at low ionic strength, i.e. 0.24 M NaCl (Figure 5A, lane 4), whereas at 2 M NaCl, stable fragments were observed (Figure 5A, lane 3).…”
Section: Resultssupporting
confidence: 87%
See 2 more Smart Citations
“…diluting the histones from 2 M NaCl solutions, were subjected to trypsin treatment, and the resulting fragments were analyzed by MS. As controls, isolated eNP (Figure 5A; lanes 1 and 2) and H3-H4 (Figure 5A; lanes 3–5) were also digested. Data show, as previously found for H2A-H2B (21), that histones were extensively digested at low ionic strength, i.e. 0.24 M NaCl (Figure 5A, lane 4), whereas at 2 M NaCl, stable fragments were observed (Figure 5A, lane 3).…”
Section: Resultssupporting
confidence: 87%
“…Moreover, when the H2A-H2B/H3-H4 mixture is extensively dialyzed against 0.24 M NaCl buffer, conditions that favor H3-H4 dimerization, the amount of the high MW complex is negligible (Figure 3D). The sedimentation profile of this sample resembles that of eNP/H2A-H2B complexes (21), suggesting that the chaperone interacts mainly with histone dimers generated on octamer/H3-H4 tetramer dissociation.
Figure 3.NP binds differently H3-H4 dimers and tetramers.
…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Because endogenous H2A is only found bound to Npm in the egg, the likely endogenous histone substrate for Prmt5-Mep50 is bound to Npm. Npm binding to histones possibly alters the conformation so that the unstructured tails of both Npm and histones may be no longer accessible for binding and methyltransferase activity (54). Furthermore, endogenous modifications on Npm, including phosphorylation and arginine methylation, substantially alter the Prmt5 activity toward histones as well.…”
Section: Discussionmentioning
confidence: 99%
“…The C-terminal intrinsically disordered domain contains a bipartite nuclear localization sequence, A2 and A3, and the extreme C-terminus containing positive amino acids (Dutta et al, 2001; Prado et al, 2004). Previous biochemical and electron microscope analyses revealed that the core is sufficient to bind histones, but the tail also engages in histone binding (Arnan et al, 2003; Ramos et al, 2014; Ramos et al, 2010; Taneva et al, 2009). The functional significance of the tail binding is unknown.…”
Section: Introductionmentioning
confidence: 99%